Mutational landscape of K-Ras substitutions at 12th position-a systematic molecular dynamics approach. Issue 4 (4th March 2022) - S, Udhaya Kumar.; R, Bithia.; D, Thirumal Kumar.; Doss, C. George Priya; Zayed, Hatem
Abstract: K-Ras is a small GTPase and acts as a molecular switch by recruiting GEFs and GAPs, and alternates between the inert GDP-bound and the dynamic GTP-bound forms. The amino acid at position 12 of K-Ras is a hot spot for oncogenic mutations (G12A, G12C, G12D, G12R, G12S, and G12V), disturbing the active fold of the protein, leading to cancer development. This study aimed to investigate the potential conformational changes induced by these oncogenic mutations at the 12 th position, impairing GAP-mediated GTP hydrolysis. Comprehensive computational tools (iStable, FoldX, SNPeffect, DynaMut, and CUPSAT) were used to evaluate the effect of these six mutations on the stability of wild type K-Ras protein. The docking of GTP with K-Ras was carried out using AutoDock4.2, followed by molecular dynamics simulations. Furthermore, on comparison of binding energies between the wild type K-Ras and the six mutants, we have demonstrated that the G12A and G12V mutants exhibited the strongest binding efficiency compared to the other four mutants. Trajectory analyses of these mutations revealed that G12A encountered the least deviation, fluctuation, intermolecular H-bonds, and compactness compared to the wildtype, which was supported by the lower Gibbs free energy value. Our study investigates the molecular dynamics simulations of the mutant K-Ras forms at the 12 th position, which expects to provide insights about the molecular mechanisms involved in cancer development, and may serve as a platform for targeted therapies against cancer. Communicated by Ramaswamy H. Sarma